The relationship between effort-reward imbalance and quality of working life among medical caregivers: mediating effects of job burnout - Qi, Huang; Hongyan, Sun; Song, He; Zhihang, Zhou; Ruiyin, Huang; Youjia, Ma; Xia, Li (Frontiers in Psychology, 2024)
Background To determine the relationship between effort-reward imbalance (ERI) and quality of working life (QWL) among medical caregivers and the mediating role of job burnout. Methods This was a cross-sectional survey. A total of 787 medical caregivers at seven hospitals from Sichuan and Chongqing, China, between May to September 2023 were included in this observational study. The General Information Questionnaire, Effort-Reward Imbalance Questionnaire (ERI), Maslach Burnout Inventory-General Survey (MBI-GS), and Quality of Working Life Scale (QWL7-32) were used for data collection. SPSS 26.0 and PROCESSv3.3 were used for all data analyses, including descriptive statistics. Results A total of 820 questionnaires were distributed, of which only 787 were valid (return rate; 95.98%). The QWL score of medical caregivers was 126.94 ± 16.69. However, QWL scores were significantly different depending on age, number of children, family support status, department, years of experience, night shift status, number of night shifts per month, number of hours worked per day, monthly income, and occurrence of errors or adverse events (p < 0.05). Furthermore, job burnout and ERI were negatively correlated with QWL (p < 0.01). Job burnout mediated (95% CI = -0.365, −0.260) the relationship between ERI and QWL, accounting for 58.65% of the total effect. Conclusion Medical caregivers have a medium level of QWL. Job burnout partially mediates the relationship between ERI and QWL. Medical caregiver managers can improve QWL by directly intervening in occupational stress and indirectly intervening in job burnout.